Piezoelectricity : evolution and future of a technology - Heywang, Walter. (Springer, 2017)
pt. 1. Basics and materials -- pt. 2. Applications and innovations -- pt. 3. Characterisation methods -- pt. 4. Multiscale modelling -- pt. 5. The future.